(untitled) (Research, Society and Development, 2022)
Since the topic of inclusion is extremely important for the reality of education in Brazil and knowing the guidelines that certify the access and permanence of people with disabilities in a school institution, this study aims to analyze the process of student inclusion autism and the importance of the teacher’s role in this student’s teaching and learning. The work is a literature review, using bibliographic research as a method. In this sense, articles, dissertations and books that address the proposed theme and which were selected from the databases Google Academic, CAPES Periodicals and Digital Library of Theses and Dissertations (BDTD) are part of the theoretical foundation of the research. Research shows that the process of including autistic students is still very slow, and it is still challenging for the school. Furthermore, it is possible to highlight that many teachers still do not know the peculiarities of the autistic student and do not understand how to work with this public. The teacher, as a mediator of knowledge, needs to go deeper into the theme of inclusion, developing methods to ensure the full participation of students with autism. For this, there are some methods available to the teacher, which help in communication and, consequently, in the inclusion of the autistic student, among them the TEACCH (Treatment and Education of Children with Autism and Disadvantages in Communication), PECS (Communication System by Exchange of Figures), ABA (Applied Behavior Analysis), Information and Communication Technologies (ICTs), Augmentative and Alternative Communication (CAA), in addition to efficient Assistive Technologies. Finally, it is concluded that there is still much to be explored and discussed in the theme of inclusive education for students with Autistic Spectrum Disorder (ASD).